EFFECT OF DEFUZZIFICATION METHODS IN SOLVING FUZZY MATRIX GAMES - Laxminarayan Sahoo (Journal of New Theory, 2015)
– This paper deals with two-person matrix games whose elements of pay-off matrix are fuzzy numbers. Then the corresponding matrix game has been converted into crisp game using different defuzzification techniques. The value of the matrix game for each player is obtained by solving corresponding crisp game problems using the existing method. Finally, to illustrate the proposed methodology, a practical and realistic numerical example has been applied for different defuzzification methods and the obtained results have been compared